2020
DOI: 10.5812/aapm.111607
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of One-Day Multiple-Choice Question Workshop for Anesthesiology Faculty Members

Abstract: Background: Multiple-choice questions (MCQs) are used commonly to evaluate medical health students. Most novice educators tend to create poor quality, flawed, and low-cognitive-level questions. Therefore, there is a need for educating the assessors to maximize the quality of MCQs and evaluations. Objectives: The current study aimed to evaluate the effect of a one-day MCQ workshop on anesthesiology faculty members. Methods: Faculty members were invited to participate in a four-hour, one-day MCQ workshop. At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Ali et al 12 documented good to excellent rating of the participants on the knowledge gained and understanding of the content of the workshop in their study. Sezari et al 13 documented in their study reported that one-day short workshop on MCQs as a faculty development program improves capacities of the faculty members revealed by the participants. Participants reported a significant improvement in item writing skills and ability to identify flawed items immediately after participation in training workshop mentioned by Beg et al 2 in their study.…”
Section: Discussionmentioning
confidence: 95%
“…Ali et al 12 documented good to excellent rating of the participants on the knowledge gained and understanding of the content of the workshop in their study. Sezari et al 13 documented in their study reported that one-day short workshop on MCQs as a faculty development program improves capacities of the faculty members revealed by the participants. Participants reported a significant improvement in item writing skills and ability to identify flawed items immediately after participation in training workshop mentioned by Beg et al 2 in their study.…”
Section: Discussionmentioning
confidence: 95%
“…10 Feedback taken immediately after another one day workshop showed that participants found the workshop to be practical and their expectations regarding MCQ development were met through this workshop. 16…”
Section: Discussionmentioning
confidence: 99%
“…Especially, considering the persistent analysis and standard direct perpetual feedbacks to the trainees followed by the assessment process, complementary results demonstrated the unignorable role for developing a scientific approach to formative and summative assessment of clinical anesthesiology residents (CAs), including training workshops, which were held by the DACC for faculty members (26-28, 50, 51). Various assessment methods were applied with their specific applications; however, they are not limited to the following methods (24,26,28,29 The results of our study regarding resident support and mentorship programs led to objective improvements in the performance of anesthesiology residents; however, these objective improvements in the residents' outcome were recorded after junior faculty members passed the Faculty Development programs (FDP), including trainee support techniques (26,27). This finding was in concordance with the majority of findings in great academic centers (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Education Indices: Teaching method (23-25); Passing comprehensive exams (23,(26)(27)(28)(29); Mentorship (26,27); Assessment methods (24,28,29); Faculty development (30,31); Professionalism in medical education (28,32); Integration in education (31,(33)(34)(35); Crisis management (32); Competency-based medical education (study in progress).…”
Section: Methodsmentioning
confidence: 99%